2008
DOI: 10.3746/jkfn.2008.37.5.605
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Wa-song (Orostachys japonicus A. Berger) According to Drying Methods

Abstract: Antioxidant activity of wa-song (Orostachys japonicus A. Berger) was analyzed to clarify the influence of extractive solvent and drying method such as sun, hot-air and freeze drying. The contents of total phenols and flavonoids were significantly higher in 95% ethanol extracts than water extracts. Ability of reducing power and DPPH radical, hydroxyl radical and nitrite scavenging ability were higher in the order of hot-air dried sample> freeze dried sample> sun dried sample and these abilities were also higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 10 publications
0
5
1
4
Order By: Relevance
“…The IC 50 values, which were calculated as the concentration of sample required to scavenge 50% of the radical species were 29.7 ± 0.34 mg/l for DPPH , 16.9 ± 0.14 mg/l for ABTS + , and 34.2 ± 0.75 mg/l for NO . Lee et al (2008) reported an IC 50 value for DPPH (554 mg/l) measured from the ethanolic extract of the O. japonicus, that was much greater than the value measured in the present work. A greater IC 50 value is indicative of lower antioxidant activity.…”
Section: Antioxidant Activitycontrasting
confidence: 75%
See 1 more Smart Citation
“…The IC 50 values, which were calculated as the concentration of sample required to scavenge 50% of the radical species were 29.7 ± 0.34 mg/l for DPPH , 16.9 ± 0.14 mg/l for ABTS + , and 34.2 ± 0.75 mg/l for NO . Lee et al (2008) reported an IC 50 value for DPPH (554 mg/l) measured from the ethanolic extract of the O. japonicus, that was much greater than the value measured in the present work. A greater IC 50 value is indicative of lower antioxidant activity.…”
Section: Antioxidant Activitycontrasting
confidence: 75%
“…Its flowers rosettes in autumn and withers in early winters, leaving a compact bud of mostly callus leaves that grow basally in spring to form callustipped foliage leaves. The water extract of the herb has been utilised traditionally as a folk medicine in the Republic of Korea for the treatment of various diseases, including fever, gingivitis, metritis, intoxication and cancers (Lee, Seo, Shin, Lee, & Sung, 2008). The various biological activities of the herb decoction have been investigated, including the calpain inhibitory effect, enhancement of hepatic alcohol dehydrogenase, protection of neuronal cells from apoptosis, and antioxidant effect Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…한국, 중국, 일본 등지에 분포하며 면역 (9), 항산화 (10,11), 항균 (12,13), 항고지혈증(14) 및 항당뇨 효과 (15) (17), HT-29 및 SW480 인간 대장 암 세포 (16,18,19), 위암, 간암, 자궁경부암 및 폐암 세포 등 다양한 암세포의 세포 성장 억제 효과 및 apoptosis 유도 효과에 대한 연구들이 보고되어 있다 (20,21 (Fig. 1, 2…”
Section: 서 론unclassified
“…와송(Wa-song, Orostachys japonicus)은 오래전부터 민 간요법으로 여러 질병의 치료를 위한 소재로 사용되어져 왔 으며, 항산화 (7)(8)(9), 항당뇨 활성(10,11)이 보고된 바 있다. 더 욱이 quercetin과 kaempferol 유도체가 와송의 총 플라보노 이드 함량에 대해 약 53%를 차지하는 것으로 보고된 바 있 는데(7), quercetin은 혈당 강하에 효과적이며 혈중 총 콜레 스테롤 및 중성지방 수준의 감소, 췌장으로부터 인슐린 분비 를 촉진시키는 것으로 알려져 있다 (12)(13)(14).…”
unclassified
“…더 욱이 quercetin과 kaempferol 유도체가 와송의 총 플라보노 이드 함량에 대해 약 53%를 차지하는 것으로 보고된 바 있 는데(7), quercetin은 혈당 강하에 효과적이며 혈중 총 콜레 스테롤 및 중성지방 수준의 감소, 췌장으로부터 인슐린 분비 를 촉진시키는 것으로 알려져 있다 (12)(13)(14). 그 외에 백복령 (Baekbokryung, Poria cocos Wolf)과 사인(Sa-in, Amomum xanthioides)은 혈당강하 효과가 있으며 (15,16) (8). 백복령, 사인 및 창출은 문헌 조사 결과 항당뇨 활성 이 있는 식물류 중 사용 빈도가 높은 식물류로 선정되었으 며, 생약재상에서 건조품을 구입하였다 (9,11).…”
unclassified